2020
DOI: 10.1200/jco.2020.38.15_suppl.505
|View full text |Cite
|
Sign up to set email alerts
|

Letrozole + ribociclib versus letrozole + placebo as neoadjuvant therapy for ER+ breast cancer (FELINE trial).

Abstract: 505 Background: Ribociclib (R) + letrozole (L) is superior to L in metastatic breast cancer (BC). Preoperative endocrine prognostic index (PEPI) score 0 after neoadjuvant endocrine therapy (NET) is associated with low risk of relapse without chemotherapy in ER+ BC. On-therapy change in Ki-67 predicts adjuvant recurrence. FELINE is a biomarker-based multicenter randomized trial comparing changes in Ki-67 and PEPI between L+ Placebo (P) & L+R. Methods: Postmenopausal women with >2 cm or node+ ER+ HER2- B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 0 publications
0
27
0
2
Order By: Relevance
“…The addition of ribociclib to letrozole during six cycles in the neoadjuvant setting was explored in the FELINE trial. It showed a higher number of patients with a complete cell cycle arrest after 2 weeks of treatment in the ribociclib group compared with the placebo group, although at surgery no difference in proportion of patients with complete cell cycle arrest was found [65]. The NeoMonarch trial showed a reduction in Ki67 when abemaciclib was added to anastrazole compared with anastrazole monotherapy after 2 weeks of treatment [66].…”
Section: Neoadjuvant Settingmentioning
confidence: 99%
“…The addition of ribociclib to letrozole during six cycles in the neoadjuvant setting was explored in the FELINE trial. It showed a higher number of patients with a complete cell cycle arrest after 2 weeks of treatment in the ribociclib group compared with the placebo group, although at surgery no difference in proportion of patients with complete cell cycle arrest was found [65]. The NeoMonarch trial showed a reduction in Ki67 when abemaciclib was added to anastrazole compared with anastrazole monotherapy after 2 weeks of treatment [66].…”
Section: Neoadjuvant Settingmentioning
confidence: 99%
“…Additionally, continuous and intermittent dose of ribociclib seem to have similar efficacy but different toxicity profiles. [105]. The adjuvant phase III trial NATALEE, aimed to delay acquired resistance to ET and to improve invasive disease-free survival (iDFS), compares the efficacy and the safety of ribociclib plus standard ET versus ET alone as adjuvant therapy for HR-positive, HER2-negative early BC and is still ongoing [106].…”
Section: Neoadjuvant/adjuvant Therapymentioning
confidence: 99%
“…The phase II FELINE trial was designed to determine whether neoadjuvant therapy with ribociclib combined with letrozole for 24 weeks increases the proportion of patients with a PEPI score of 0 at surgery, compared with single agent letrozole. Preliminary results did not show any difference between the two treatment arms [ 89 ].…”
Section: Targeted Therapiesmentioning
confidence: 99%